A comparison between thoracic epidural analgesia and rectus sheath catheter analgesia after open midline major abdominal surgery: randomized clinical trial. Issue 3 (11th May 2022) - Krige, Anton; Brearley, Sarah G.; Mateus, Céu; Carlson, Gordon L.; Lane, Steven
Abstract: Background: Rectus sheath catheter analgesia (RSCA) and thoracic epidural analgesia (TEA) are both used for analgesia following laparotomy. The aim was to compare the analgesic effectiveness of RSCA with TEA after laparotomy for elective colorectal and urological surgery. Methods: Patients undergoing elective midline laparotomy were randomized in a non-blinded fashion to receive RSCA or TEA for postoperative analgesia at a single UK teaching hospital. The primary quantitative outcome measure was dynamic pain score at 24 h after surgery. A nested qualitative study (reported elsewhere) explored the dual primary outcome of patient experience and acceptability. Secondary outcome measures included rest and movement pain scores over 72 h, functional analgesia, analgesia satisfaction, opiate consumption, functional recovery, morbidity, safety, and cost-effectiveness. Results: A total of 131 patients were randomized: 66 in the RSCA group and 65 in the TEA group. The median (interquartile range; i.q.r.) dynamic pain score at 24 h was significantly lower after TEA than RSCA (33 (11–60) versus 50.5 (24.50–77.25); P = 0.018). Resting pain score at 72 h was significantly lower after RSCA (4.5 (0.25–13.75) versus 12.5 (2–13); P = 0.019). Opiate consumption on postoperative day 3 (median (i.q.r.) morphine equivalent 17 (10–30) mg versus 40 (13.25–88.50) mg; P = 0.038), hypotension, or vasopressor dependency (29.7 versus 49.2 per cent; P = 0.023) and weight gain to day 3 (median (i.q.r.) 0 (−1–2) kg versus 1 (0–3) kg; P = 0.046) were all significantly greater after TEA, compared with RSCA. There were no significant differences between groups in other secondary outcomes, although more participants experienced serious adverse events after TEA compared with RSCA, which was also the more cost-effective. Conclusions: TEA provided superior initial postoperative analgesia but only for the first 24 h. By 72 hours RSCA provides superior analgesia, is associated with a lower incidence of unwanted effects, and may be more cost-effective. Abstract : Thoracic epidural analgesia provided superior initial postoperative analgesia compared with rectus sheath catheter analgesia (RSCA) but only for the first 24 h. By 72 h, RSCA provides superior analgesia and is also associated with a lower opiate consumption on postoperative days 3 and 4, lower incidence of unwanted effects (adverse events and hypotension), greater patient satisfaction, and may be more cost-effective.